Bibliometric Waqf Management in Indonesia - Heppy Purbasari; Bawono, Andy Dwi Bayu; Rangga Handika; Triyono (Riset Akuntansi dan Keuangan Indonesia, 2023)
A significant quantity of abandoned waqf lands in Indonesia is evidence that the optimal management of waqf has yet to be achieved. The primary objective of this study is to identify and analyze the existing research lacunae in prior studies, hence facilitating the delineation of future research directions. The employed research methodology utilizes a quantitative approach, wherein publications are quantified using the publish or perish tool and analyzed using the Vosviewer software afterward. This study employs the terms "waqf management" OR "waqf management" AND Indonesia to search for papers inside the Scopus database, focusing on the research period from 2015 to 2022. The study yielded a total of 14 papers about the management of waqf. These articles were categorized into four distinct research areas, namely: (1) the enhancement of productive waqf, (2) the administration of the waqf system, (3) the legal aspects of waqf, and (4) crowdfunding through Sukuk. Based on the four themes above, it is evident that the advancement of productive waqf has been implemented throughout many waqf institutions in Indonesia, yielding favorable outcomes in enhancing the socio-economic conditions of impoverished individuals.